INTEGRATIVE FUNDING AND EFFECTIVE IMPLEMENTATION OF UNIVERSAL BASIC EDUCATION PROGREMME: A NEED ASSESSMENT IN PRIMARY AND JUNIOR SECONDARY SCHOOLS OF EBONYI STATE, NIGERIA - Adali A., Onele; Uzoma, Aja-Okorie (European Scientific Journal, ESJ, 2013)
This study was an assessment on the extent of integrative funding for the effective implantation of universal basic education (UBE) programme in Ebonyi state, Nigeria. In carrying out the study, a descriptive survey design was adopted by the researchers. Three research questions and two hypotheses were posed to guide the study. The population of the study was comprised of 228 principals and 1036 primary school head teachers in Ebonyi state. A 30 0/0 sample size of 59 principals and 311 primary school head teachers were randomly drawn making the sample to be 370 research respondents. The instruments for data collection were self structured questionnaire which was based on face and content values. The reliability of the instrument was established through test re-test method and the statistical tools used to analyze the results was Pearson product moment and it yielded a reliability co-efficient of 0.75. Mean and standard deviation were employed in the analysis of the data based on the research questions. While t-test of difference was used to analyze the two hypotheses at 0.05 significant level. The study revealed that government contributed to a great extent but not enough for effective implementation of UBE programme. The study also showed that local donor agencies contributed insignificantly to the effective implementation of UBE programme in Ebonyi state. Also, that international donor agencies contribute to a low extent in the provision of instructional material, sports and health equipment, furniture and classroom blocks for the implementation of UBE programme. Based on the findings, it was recommended that government should maintain the policy of allotting at least 26 percent of the entire budget to education hence, adequate fund for UBE implementation, and ensure there are committed body to see to the prudent management of such fund. Government should devise a way of holding a regular or routine meetings with the various stake holders, parents and other voluntary agencies for them to be committed towards UBE funding in Ebonyi State etc.